The interaction of predator prey with uncertain initial population sizes (Interaksi pemangsa-mangsa dengan saiz awal populasi tak pasti) - Almbrok Hussin Alsonosi Omar; Yahya Abu-Hasan (Penerbit Universiti Kebangsaan Malaysia, 2011)

(untitled)
﻿Differential model of dynamical predator-prey system contains some factors that constitute a formal description of features of the interaction between the predator and its prey. The initial population sizes are the factors which affect the behaviour of the predator-prey interaction. These factors may not be uniquely defined. In this paper we study the effect of uncertain initial population sizes of predator and prey on the behaviour of predator-prey interaction. Results based on numerical simulations are discussed.